Activation of caspase-like proteases and induction of apoptosis by isopentenyladenosine in tobacco BY-2 cells - Mlejnek, Petr; Procházka, Stanislav (Planta, 2002)
The effects of isopentenyladenosine (iPA) on tobacco (Nicotiana tabacum L.) BY-2 cells were examined. The number of BY-2 cells decreased in a time- and concentration-dependent manner after being exposed to micromolar concentrations of iPA. This decrease was mainly due to a loss of cell viability, since no substantial changes in cell cycle progression were revealed by flow-cytometric analysis. Dying cells exhibited the typical morphological and biochemical hallmarks of apoptosis, including cell shrinkage, chromatin condensation, and degradation of nuclear DNA to nucleosomal size fragments. Caspase-1-like and caspase-3-like proteases also became activated, the former being dominant. Inhibitor-sensitivity studies revealed that although synthetic caspase inhibitors failed to prevent cell death they markedly reduced cell death in tobacco BY-2 cells, Nu-benzyloxycarbonyl-Val-Ala-Asp-fluoromethylketone, a specific inhibitor for caspase-1, being the most effective. Our results indicate that caspase-like proteases, and particularly caspase-1-like protease, might be critically implicated in iPA-induced apoptosis of BY-2 cells. Finally, the outcome of inhibiting adenosine kinase by 4-amino-3-iodo-1(beta- D-ribofuranosyl)pyrazolo[3,4-d]-pyrimidine revealed that intracellular phosphorylation of iPA is required for its cytotoxicity to develop.
Keywords: chloromethylketony aminokyselin; Cytokinins; cytokininy; kultivované buňky; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; apoptóza; Oligopeptides; Caspase Inhibitors; kaspasa 3; kaspasy; oligopeptidy; Amino Acid Chloromethyl Ketones; regulátory růstu rostlin; Endopeptidases; Caspase 1; endopeptidasy; Caspases; Cells, Cultured; Enzyme Activation; tabák; kaspasa 1; Caspase 3; inhibitory kaspas; aktivace enzymů; Isopentenyladenosine; isopentenyladenosin; Plant Growth Regulators; Nicotiana; Apoptosis